2021
DOI: 10.20511/pyr2021.v9n2.1202
|View full text |Cite
|
Sign up to set email alerts
|

¿Se publican las tesis sustentadas de psicología en el Perú? Un análisis de tres universidades mejor posicionadas en el ranking Scimago

Abstract: Con el objetivo de determinar las características y la frecuencia de publicación de tesis de psicología de tres universidades peruanas con mejor posicionamiento en el ranking Scimago, se realizó un estudio descriptivo de análisis de documentos sobre 180 tesis de pregrado aprobadas en el periodo 2010 – 2019. La búsqueda de artículos se realizó en Google Académico y la base de datos de Scopus. Los resultados indican que las tesis en mayor proporción son de tipo correlacional (53,3%), orientados a una línea de ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
1
3
0
2
Order By: Relevance
“…In this sense, the different topics are predominantly framed within the clinical and health psychology line of research. This, has also been seen in previous studies in Peru, where this line of research was the most frequent (8).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In this sense, the different topics are predominantly framed within the clinical and health psychology line of research. This, has also been seen in previous studies in Peru, where this line of research was the most frequent (8).…”
Section: Discussionsupporting
confidence: 88%
“…A study on lines of research in Colombian universities also indicated that clinical psychology was one of the most investigated by different research groups (20). This finding, regardless of the type of research, is important if one takes into consideration that the frequency of lines of research that include mental health as a priority of study in Peruvian universities is low (8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…De esta manera, las facultades de ciencias de la salud deberían contar con recursos humanos calificados para la investigación, con ello asegurar el desarrollo del conocimiento científico y tecnologico en el ámbito de la salud (Cheol et al, 2020). Desafio aun imperante en el Perú, ya que reportes iniciales dan cuenta de que incluso las universidades que lideran los rankings no aseguran que los productos científicos se difundan a travez de publicaciones periodicas (Mamani-Benito et al, 2021b).…”
Section: Discussionunclassified